An adolescent with recurrent ankle swelling. Issue 6 (2nd March 2020) - Trombetta, Andrea; Genovese, Maria Rita Lucia; Gortani, Giulia; Barbi, Egidio
Abstract : A 14-year-old girl was admitted to our institute with a history of intermittent bilateral ankle swelling, and moderate but progressively worsening pain which has lasted for 2 years. The patient's history was unremarkable. She did not take medications and was not involved in any sports activity. She reported no fever, gastrointestinal symptoms, fatigue, weight loss, travels abroad or previous infections. She reported moderate pain at night, associated with a sense of heaviness, tightness and general discomfort, and with no response to ibuprofen. Physical examination was remarkable only for bilateral ankle non-pitting oedema, more evident on the left leg, with a thickened skinfold at the base of the second toe, and without redness, swelling or skin warming. The patient had been previously examined, and her foot and ankle X-rays, ultrasound (US) and MRI were all negative. Blood tests (white cell count, C reactive protein, erythrocyte sedimentation rate, albumin, antinuclear antibodies, creatinine, transaminase, creatine kinase, lactate dehydrogenase, thyroid function and glucose) and urinalysis were in the normal range. Her ocular assessment and echocardiogram were also normal. Question 1: Based on the clinical picture and laboratory tests, what is the most likely diagnosis? Deep venous thrombosis. Osteochondritis. Lymphoedema. Juvenile idiopathic arthritis. Question 2: Based on what you see in figure 1, what is the underlying cause? Recurrent bacterial lymphangitis. Primary lymphoedema. Tumour. Filariasis. Question 3: Which is the best diagnostic test to confirm the diagnosis? US scan. MRI. Lymphoscintigraphy. Reassurance and clinical follow-up. Question 4: What is the mainstay of management of this condition? Wait and see. Antibiotic course. Supportive therapy (ie, physical activity, elevation of extremities, pneumatic compression). Surgical intervention. Answers can be found on page 2.